Hydrogen Atom Transfer (HAT): A Versatile Strategy for Substrate Activation in Photocatalyzed Organic Synthesis. Issue 15 (2nd March 2017) - Capaldo, Luca; Ravelli, Davide
Abstract : The adoption of hydrogen atom transfer (HAT) in a photocatalytic approach, in which an excited catalyst is responsible for substrate activation, offers unique opportunities in organic synthesis, enabling the straightforward activation of R–H (R = C, Si, S) bonds in desired reagents. Either a direct strategy, based on the intrinsic reactivity of a limited number of photocatalysts in the excited state, or an indirect one, in which a photocatalytic cycle is used for the generation of a thermal hydrogen abstractor, can be exploited. This microreview summarizes the most recent advances (mainly from the last two years) in this rapidly developing area of research, collecting the selected examples according to the nature of the species promoting the HAT process. From the synthetic point of view, this area has led to the development of a plethora of strategies for C–C, C–Si, C–N, C–S, and C–halogen (particularly, fluorine) bond formation, as well as for oxidation reactions. Abstract : Photocatalytic approaches involving the activation of substrates through hydrogen atom transfer (HAT) offer unique opportunities in organic synthesis. This microreview summarizes the most recent advances in this rapidly developing area, collecting the selected examples according to the nature of the species promoting the HAT process.